Genome-Wide Identification and Expression Profiling of the COMMD Gene Family in Four Bivalve Molluscs - Chen, Xiaomei; Hu, Naina; Lian, Shanshan; Li, Luoan; Sun, Fengzhi; Zhang, Lingling; Wang, Shi; Bao, Zhenmin; Hu, Jingjie (Frontiers in Marine Science, 2022)
The COMMD (copper metabolism gene MuRR1 domain) gene family, highly conserved among multicellular eukaryotic organisms, plays important roles in a variety of biological processes, ranging from copper homeostasis, ionic transport, protein trafficking, NF-κB-mediated transcription, and cell proliferation. However, systematic identification, spatiotemporal expression, and stress-responsive patterns of COMMD genes remain obscure in molluscs. Here, we analyzed the characteristics of the COMMD gene family in four bivalve molluscs based on both genome and extensive transcriptomic resources. Firstly, we investigated the genomic signatures, functional domains, and phylogenetic relationships, and ten single-copy members were identified in Yesso scallop (Patinopecten yessoensis), Zhikong scallop (Chlamys farreri), Pacific oyster (Crassostrea gigas), and dwarf surf clam (Mulinia lateralis), respectively. Strong purifying selection was revealed for COMMD4. Higher expressions of most COMMDs were observed in the hepatopancreas, besides which a different tissue preference of COMMDs’ expression was found among four bivalves. Moreover, in the dwarf surf clam, the responses of COMMD members under stresses were found more sensitive in the hepatopancreas than in the gill, and MlCOMMD9 and MlCOMMD4 might be the good candidate stress indicator genes respectively for copper ion stress and V. Anguillarum infection. Our study would contribute to a better understanding for the evolution of the COMMD gene family and provide valuable information for their innate immune roles in bivalve molluscs.